Facile and Scalable Synthesis of Ag Nano‐Flowers that Can be Sintered Below 120 °C. Issue 26 (17th August 2022) - Guo, Zeliang; Lang, Jialiang; Zhang, Haitian; Yang, Cheng; Lin, Sen; Wu, Hui
Abstract: Silver particles are key materials for the production of conductive inks, which are typically thermally sintered to obtain high conductivity. However, it remains a big challenge to achieve high conductivity at temperatures lower than 150 °C, for the protection of heat‐sensitive components in printed electronic devices. In this study, a novel frigid synthesis strategy at subzero temperature (Celsius) to produce Ag NPs with rich, rose‐like nanostructures (Ag nano‐flowers) is developed. The growth mechanism of Ag nano‐flowers under frigid conditions is analyzed and discussed. Due to the fine nanoscale structure of Ag nano‐flowers, they exhibit low sintering temperature below 120 °C. The electrical conductivity of printed Ag nano‐flower foil reaches 8.64 × 10 4 S cm −1 at 120 °C, and 1.20 × 10 5 S cm −1 at 150 °C. This study provides an attractive approach to the facile fabrication of Ag nano‐flowers with high electronic conductivity sintered at low temperatures and grants new insights into nanocrystallization under low‐temperature conditions. Abstract : Easily sintered, highly conductive Ag nano‐flowers are fabricated with frigid synthetic strategy as a promising conductive material for applications in printed electronics. The method is simple yet wildly applicable. Ag nano‐flowers can be sintered below 120 °C, and conductivity of Ag nano‐flower ink reaches 1.20 × 10 5 S cm −1 at 150 °C.